2010
DOI: 10.3928/01484834-20100730-02
|View full text |Cite
|
Sign up to set email alerts
|

Frameworks for Patient Safety in the Nursing Curriculum

Abstract: Patient safety has recently received a great deal of media coverage. Professional and regulatory agencies have indicated that patient safety education should be provided to health care workers to improve health outcomes. This study’s primary purpose was to gain a better understanding of the current status of patient safety awareness among prelicensure nursing students. Data were collected from two samples ( N = 150 and 318), and nursing curricula were examined from seven institutions. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 64 publications
0
78
1
2
Order By: Relevance
“…[9][10][11] Historically, nursing has always been a patient focused profession that has placed great emphasis on patient care and outcomes. [12] The nursing regulatory body in Ontario is the College of Nurses of Ontario (CNO) and it has developed professional standards that encompass entry-to-practice competencies to ensure that nurses that enter the practice domain are competent to provide safe care.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Historically, nursing has always been a patient focused profession that has placed great emphasis on patient care and outcomes. [12] The nursing regulatory body in Ontario is the College of Nurses of Ontario (CNO) and it has developed professional standards that encompass entry-to-practice competencies to ensure that nurses that enter the practice domain are competent to provide safe care.…”
Section: Introductionmentioning
confidence: 99%
“…RNs involved in medication errors may feel alone, ashamed, and unsupported. Literature suggests that RNs may not report medication errors due to fear of punitive measures, fear of being perceived as incompetent, and a wish to maintain positive collegial relationships (Chenot & Daniel 2010). The RN involved in a medication error may not wish to selfreport the error due to fear of being perceived as an outsider, or the one who did not possess enough knowledge or experience to avoid such an error.…”
Section: Emerging Leader Perspectivementioning
confidence: 99%
“…The number of participants from the associate degree programs was small with the research results reported jointly among both program types (Chenot & Daniel, 2010;Smith, Cronenwett, & Sherwood, 2007). Safety research has focused on student perspectives of safety knowledge taught in curricula (Sullivan, Hirst, & Cronenwett, 2009).…”
Section: Literature Gapsmentioning
confidence: 99%
“…Patient safety curricula analysis revealed that each of the participating nursing schools incorporated three of the six core QSEN competencies with one school integrating all six QSEN competencies (Chenot & Daniel, 2010).…”
Section: Quality and Safety Education For Nursesmentioning
confidence: 99%
See 1 more Smart Citation